(3GdJhMjOs - (3CHh YHO Gddg, CHh eMeO, GdeaVd Hf YeQ GdLYaj Gdchajs
(3ChdgG (B:s
(3HSe Gddg (B... (3Qhi eMeO Hf SfGf bGd MOKfj GdeaVd Hf YeQ bGd cfJ PGJ jhe HYO GdYUQ LGdjSG a GdQhVI Hjf GdbHQ hGdefHQ hCfG eacQ ajeG NU Gddg Hg SjOfG eMeO ef GdTQa hGdaVGFd heG efMg hCYWGg hTQag hMHGg eGdG jYQag GdLeghQ (B...s
(3BNQgG (B:s
.. (3aGfJ efG HGdecGf GdQajY hehVYc ef bdhH GdeDefjf ehVY GdeGA ef GdUOi hdG JSCdf YeG hYOJc MJi CMOK dc efg PcQi bGd GdeaVd aGfUQaJ ef YfO ehdGj Yde dG jfUQa CMO HeKdg (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B4 / 351 ( 2156)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds